'Come here, it sang, listen': Juliana Spahr's commons poetics in That Winter the Wolf Came. Issue 7 (3rd July 2021) - Kabo, Raphael
ABSTRACT: The work of contemporary American poet, critic, and essayist Juliana Spahr is concerned with politically charged questions of connection, collectivity, and community across disparate ontological domains and ecological boundaries. This essay argues that Spahr's 2015 poetry collection That Winter the Wolf Came, which has to date garnered less critical attention than her previous work, combines lyric, intertextual reference, asequential narrative, parataxis, and other formal techniques and compositional practices into a commons poetics . This poetics, in turn, allows Spahr to effectively represent a commons which finds space for plural subjects as diverse as the activists of the 2011–2012 Occupy Movement, oil rigs, and Brent geese. Despite Spahr's own fundamental reservations about the political efficacy of poetry, her unique use of lyric, in particular, cultivates radical connections and oppositional tactics for these plural subjects, offering a vision of a utopian commons beyond capitalism.